2015
DOI: 10.1017/s0022377814001299
|View full text |Cite|
|
Sign up to set email alerts
|

Microwave discharge initiated by double laser spark in a supersonic airflow

Abstract: In this paper, we report the results of an experimental study of microwave (MW) discharge in the supersonic flow initiated by the laser spark and numerical simulation of multiple laser spark shockwave structures in airflow. The MW discharge initiation has been produced by single and double laser sparks. By using different spatial and temporal configuration of laser sparks in supersonic flow, we demonstrate the feasibility of an MW breakdown threshold decrease and control over shape and location of MW plasma. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The works [72,95,96], presented by V. Lashkov's group, are ideologically a continuation of the previous work. The authors present experimental results on MW discharge in a supersonic flow initiated by single and double LSs, along with numerical simulations of the SW structures induced by multiple LSs in an airflow (Figure 26).…”
Section: Flow Control Using Combined Physical Phenomenamentioning
confidence: 66%
See 2 more Smart Citations
“…The works [72,95,96], presented by V. Lashkov's group, are ideologically a continuation of the previous work. The authors present experimental results on MW discharge in a supersonic flow initiated by single and double LSs, along with numerical simulations of the SW structures induced by multiple LSs in an airflow (Figure 26).…”
Section: Flow Control Using Combined Physical Phenomenamentioning
confidence: 66%
“…This MW discharge was localized at electric field maxima generated by a customdesigned focusing system in an experiment. The authors comprehensively determined all the critical parameters of the MW discharge plasma and captured images of elongated plasmoids aligned with the supersonic flow axis ( [72] by R. Khoronzhuk) (Figure 16).…”
Section: Multi-component Plasma Structures: Experimental Obtaining An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 51 illustrates the effectiveness of this technique with the plasma discharge showing clear preference to the pre-ionised rectangular region. The ability to locate the microwave plasma discharge through focused laser energy deposition is further shown by Khoronzhuk et al 134 The authors compared single laser pulse sparked microwave discharge with double pulse microwave discharge. They showed that elongation of the plasma discharge that can be achieved through multiple laser pulses.…”
Section: Subcritical Plasma Generation (Laser Sparked)mentioning
confidence: 97%
“…Meanwhile, a powerful microwave generator is required at the atmospheric pressure when the breakdown takes place at the energy density larger than 10 6 W/cm 2 . A volume microwave discharge is used in the ignition systems [20] and combustion sta-bilizers [21]. The study [22] investigates experimentally the minimum energy necessary to ignite a premixed air-methane mixture.…”
Section: Introductionmentioning
confidence: 99%